Peran E- Commerce Dalam Meningkatkan Pendapatan Penjualan Dalam Perspektif Islam - Abd Aziz; Abd Ghafur; Hofifah Hofifah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2023)
Electronic commerce is a term that is often used today for transactions online or related to the Internet. In another opinion, e-commerce is a form of media for distributing, buying, marketing, and selling goods or services through internet electronic systems. The development of e-commerce - commerce cannot be separated from the growth rate of the Internet because e-commerce is under the Internet network. The rapid growth of the internet has made a new change in people's lives and the internet has made the internet an effective medium for business people to sell their various products. This research is a type of qualitative research, using a case study approach (Case Study), in this study using several stages in data collection in the field, namely describing existing data, and in the form of data that describes in detail, the purpose of this study is to find out how the role of e-commerce in increasing sales revenue and e-commerce in an Islamic perspective. The results of this study are that the role of e-commerce in increasing sales revenue is very important for sales and of course, transactions carried out in accordance with Islam.